Isolation and molecular characterization of the histone methyltransferase EHMT from the soft tick Ornithodorous moubata - Delana Mudiyanselage, Sewmi M. A. (Jihočeská univerzita, 2018)
The aim of this thesis was to isolate and characterize the histone methyltransferase EHMT from Ornithodoros moubata.
Isolation and molecular characterization of the histone methyltransferase EHMT from the soft tick Ornithodorous moubata
Keywords: Generalities and taxonomy of ticks; tick life cycle; epigenetics; tick epigenetics; histone methyltransferases.; Generalities and taxonomy of ticks; tick life cycle; epigenetics; tick epigenetics; histone methyltransferases.